APPLICATION OF PROMOTION TOOLS IN HOSPITALITY AND TOURISM INDUSTRY AND ITS ROLE IN DEVELOPING THE JAMMU AND KASHMIR AS A TOURIST DESTINATION - BUJDOSÓ, Zoltán; MANHAS, Parikshat Shing; -, RAMJIT; DÁVID, Lóránt; NEDELEA, Alexandru (Revista de turism - studii și cercetări în turism, 2014)
The proposed study will mainly attempt to study the promotional tools undertaken by different hotels and tour operators, and evaluate how they have been able to develop tourism and hospitality industry in the state. A survey questionnaire was used to collect primary data. Our study revealed that the main reason of not succeeding and overcoming the problem of rebuilding the state as a tourists destination after the period of militancy and others problems mainly lies within the negligence of tourism authorities not following appropriate marketing activities ; inappropriate measures and wrong allocation of promotional funds also contribute to the problem.